New Insights From MRI and Cell Biology Into the Acute Vascular-Metabolic Implications of Electronic Cigarette Vaping - Wehrli, Felix W.; Caporale, Alessandra; Langham, Michael C.; Chatterjee, Shampa (Frontiers in Physiology, 2020)
The popularity of electronic cigarettes (e-cigs) has grown at a startling rate since their introduction to the US market in 2007, with sales expected to outpace tobacco products within a decade. Spurring this trend has been the notion that e-cigs are a safer alternative to tobacco-based cigarettes. However, the long-term health impacts of e-cigs are not yet known. Quantitative magnetic resonance imaging (MRI) approaches, developed in the authors’ laboratory, provide conclusive evidence of acute deleterious effects of e-cig aerosol inhalation in the absence of nicotine in tobacco-naïve subjects. Among the pathophysiologic effects observed are transient impairment of endothelial function, vascular reactivity and oxygen metabolism. The culprits of this response are currently not fully understood but are likely due to an immune reaction caused by the aerosol containing thermal breakdown products of the e-liquid, including radicals and organic aldehydes, with particle concentrations similar to those emitted by conventional cigarettes. The acute effects observed following a single vaping episode persist for 1-3 hours before subsiding and are paralleled by build-up of biological markers. Sparse data exist on long-term effects of vaping, and it is likely that repeated regular exposure to e-cig aerosol during vaping will lead to chronic conditions since there would be no return to baseline conditions as in the case of an isolated vaping episode. This brief review aims to highlight the potential of pairing MRI, with its extraordinary sensitivity to structure, physiology and metabolism at the holistic level, with biologic investigations targeting serum and cellular markers of inflammation and oxidative stress. Such a multi-modal framework should allow interpretation of the impact of e-cigarette vaping on vascular health at the organ level in the context of the underlying biological alterations. Applications of this approach to the study of other lifestyle-initiated pathologies including hypertension, hypercholesterolemia and metabolic syndrome are indicated.